Henri Bergson’s Open Society: The Transformation of Humanity in Two Sources of Morality and Religion - Lovasz, Adam (Cosmos and History: The Journal of Natural and Social Philosophy, 2023)
In this article, I propose a reading of Henri Bergson’s Two Sources of Morality and Religion, centering on how mysticism transforms homo sapiens. For Bergson, the mystics are exemplars of social innovation, representatives of a „new species.” The open society, far from being a distant utopian social ideal, is already immanent to static, closed society. Openness can be achieved now, in the moment of mystical experience, defined by Bergson as unity with the flow of life. Instead of a rigid dualism between closure and openness, Bergson proposes that social change is driven from the inside by new moral ideas. Moral heroes are those willing to break the mould of social obligation. A form of non-discriminatory love is possible, going beyond the inner/outer distinction. Far from being a passive or contemplative practice, mysticism for Bergson is an active change of the human condition, a passage to the more-than-human.